2018
DOI: 10.2478/zireb-2018-0020
|View full text |Cite
|
Sign up to set email alerts
|

When Consumers are in Doubt, You Better Watch Out! The Moderating Role of Consumer Skepticism and Subjective Knowledge in the Context of Organic Food Consumption

Abstract: Despite numerous scholarly attempts, there is a lack of consensus regarding the relevance of various factors influencing consumer’s intention to purchase organic food. The purpose of this study is to asses the impact of subjective and personal norms on consumer attitude toward buying organic food. Moreover, this study aims to explore the moderating role of contextual factors - product knowledge and consumer scepticism on the norms- attitude link. Data were collected through an online survey on a sample of 212 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 31 publications
1
10
1
Order By: Relevance
“…Therefore, this paper focuses on the intensity of the purchase intention: a small number of samples with no purchase intention were excluded in the empirical study, and 1113 samples were used in the regression analysis. According to the previous hypotheses and empirical research experience, the dependent variable (purchase intention) was set to the classified ordered continuous variable [1][2][3][4][5], and the ordered Logit model (Ologit) was used to estimate in this paper.…”
Section: Data Sources and Model Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this paper focuses on the intensity of the purchase intention: a small number of samples with no purchase intention were excluded in the empirical study, and 1113 samples were used in the regression analysis. According to the previous hypotheses and empirical research experience, the dependent variable (purchase intention) was set to the classified ordered continuous variable [1][2][3][4][5], and the ordered Logit model (Ologit) was used to estimate in this paper.…”
Section: Data Sources and Model Selectionmentioning
confidence: 99%
“…With the prominence of environmental and food safety problems, the practice of organic agriculture and organic food have aroused great interest in the past decades [1]. The consumption of organic food is regarded as a kind of pro-environmental behavior because of its benefits to environmental protection, public health and the interests of future generations [2,3], and has gradually become a new fashion trend [4]. Organic farming is now carried out in 178 countries according to relevant reports, and global sales have increased from $7.9 billion in 2000 to $89.7 billion in 2016 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that when consumers have more knowledge of organic food, they become more dependent on themselves in forming their attitudes, and subsequently making decisions. In other words, consumer knowledge has a moderating effect on the impact that attitudes have on organic food purchase decisions [67]. The higher the level of knowledge of consumers, the more confident they are in their behavior [65].…”
Section: Consumer Knowledgementioning
confidence: 99%
“…Secondly, this study contributes an extension to the TPB model. The TPB model is often used to analyze consumers' sustainable consumption [35], 'green' consumption [49], and organic food consumption [67], but it is rarely used to study the waste classification behavior of consumers. In particular, waste classification has been widely implemented in China, and the extended TPB model helps in the in-depth study of the behavioral mechanisms around waste classification.…”
Section: Contributions To Theory and Researchmentioning
confidence: 99%
See 1 more Smart Citation